A non-decoupled backstepping control for fixed-wing UAVs with multivariable fixed-time sliding mode disturbance observer. (February 2019) - Han, Yang; Li, Peng; Zheng, Zhiqiang
This paper addresses the issue of controlling the attitude together with the airspeed of a fixed-wing unmanned aerial vehicle (UAV) in a vector manner. A novel vector control structure is proposed to provide an extension of the well-known conventional three single channels. The rigid body dynamics are established in the form of vectors, which are the velocity vector and angular velocity vector in a body-fixed coordinate frame. Vector backstepping control and multivariable fixed-time sliding mode disturbance observers are then proposed on the dynamics to ensure that the disturbances and uncertainties can be estimated and cancelled in a fixed time, and the states of the system are driven towards the expected manifolds, and stay there for all future times. The simulation results illustrate the effectiveness of the proposed approach.